2018
DOI: 10.1111/lcrp.12131
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural verbal deception

Abstract: Background. 'Interviewing to detect deception' research is sparse across different Ethnic Groups. In the present experiment, we interviewed truth tellers and liars from British, Chinese, and Arab origins. British interviewees belong to a low-context culture (using a communication style that relies heavily on explicit and direct language), whereas Chinese and Arab interviewees belong to high-context cultures (communicate in ways that are implicit and rely heavily on context). Method.Interviewees were interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 46 publications
11
67
0
Order By: Relevance
“…This speculation fits with assertions that individuals from collectivistic cultures report less specific and more generic details than individuals from individualistic cultures (Millar, Serbun, Vadalia, & Gutchess, ; Wang & Ross, ). Similar results have been observed in research on deception detection, showing interviewees in individualistic cultures typically report more explicit details than interviewees from collectivistic cultures (Leal et al, ). Leal et al () argued that interviewees from collectivistic cultures tend to leave many things unsaid, allowing the context to communicate what is implied, whereas in individualistic cultures, the communication style tends to be more explicit.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This speculation fits with assertions that individuals from collectivistic cultures report less specific and more generic details than individuals from individualistic cultures (Millar, Serbun, Vadalia, & Gutchess, ; Wang & Ross, ). Similar results have been observed in research on deception detection, showing interviewees in individualistic cultures typically report more explicit details than interviewees from collectivistic cultures (Leal et al, ). Leal et al () argued that interviewees from collectivistic cultures tend to leave many things unsaid, allowing the context to communicate what is implied, whereas in individualistic cultures, the communication style tends to be more explicit.…”
Section: Discussionsupporting
confidence: 82%
“…Similar results have been observed in research on deception detection, showing interviewees in individualistic cultures typically report more explicit details than interviewees from collectivistic cultures (Leal et al, ). Leal et al () argued that interviewees from collectivistic cultures tend to leave many things unsaid, allowing the context to communicate what is implied, whereas in individualistic cultures, the communication style tends to be more explicit. Therefore, during investigative interviews, it may be necessary to prompt and encourage eyewitnesses from collectivistic cultures to elaborate further on the initial information they provide.…”
Section: Discussionsupporting
confidence: 82%
“…That means that we did not replicate Leal, Vrij, Vernham, et al . 's () findings that truth tellers reported more verifiable sources than liars. In all other research concerning the VA to date, verifiable details rather than verifiable sources were examined and truth tellers typically reported more verifiable details than liars (Vrij & Nahari, ).…”
Section: Discussionmentioning
confidence: 99%
“…Leal, Vrij, Vernham, et al . () found that truth tellers reported more verifiable sources than liars.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation